Perceptions of non-successful families attending a weight-management clinic. Issue 4 (2nd November 2020) - Cox, Jennifer S; Searle, Aidan J; Hinton, Elanor C; Giri, Dinesh; Shield, Julian P H
Abstract : Objective: This study seeks to understand family's perceptions of their care at a paediatric weight management service, with a view to informing service improvement. Design: A qualitative service review conducted via semistructured interviews with parents (n=11) and children (n=3) who attended the clinic. The recruitment was open to all, but those who were not succeeding in their weight-loss goals self-selected to participate. Self-Determination Theory was used as a framework to explore families' experiences of the clinic. Setting: Recruitment occurred during clinical appointments and interviews were conducted over the phone in the days following the appointments. Patients: The service sees paediatric patients with a body mass index >99th percentile, with comorbidities or safeguarding concerns. Interventions: The clinic's service includes appointments typically every 2 months, with a multidisciplinary team including consultant endocrinologists, a dietician, a clinical psychologist, a social worker and a clinical nurse specialist. Main outcome measures: Families' feedback on the multi-disciplinary team (MDT) clinic, and their perceptions of how improvements could be made. Results: Families perceive a lack of autonomy, competency and feel a lack of connectivity both in their lives broadly and within their experience at the clinic. Conclusions: Interventions in families struggling with weight improvements should see the clinical team placing more emphasis on working alongside parents to develop young people's sense of self-determination. Expectations must be set that success originates from changes outside of clinical appointments and that the clinical team is in place to support the family's development of sustainable, self-determined lifestyle habits.